Palm press fibre and rice straw for cultivation grey oyster mushroom (Pleurotus sajor-caju) - Laila Naher,; Nur Aizzah Mazlan,; Nurul Adibah Hamzah,; Sainul Islam,; Siti Maryam Salamah Ab Rhaman, (Penerbit Universiti Kebangsaan Malaysia, 2022)
Sawdust (SD) usually sourced from rubber plant is commonly used as substrate to cultivate the grey oyster mushroom Pleurotus sajor-caju in Malaysia. However, the market price of SD is increasing because of its declining availability. Thus, this study aimed to discover an alternative substrate to cultivate grey oyster mushroom. The raw materials used in the substrate were oil palm pressed fiber (PPF), rice straw (RS) and SD, either alone or in combination with different ratios including T1: 90% SD + 10% rice bran (commercial substrate as control); T2: 30% RS + 20% SD + 50% PPF; T3: 50% RS + 50% PPF; T4: 100% RS; and T5: 100% PPF. The suitability of the substrates was determined based on growth, yield, nutrition and mineral content in the mushrooms. The growth and yield of the mushroom fruiting body on the different substrates showed significant differences. The shortest harvesting day was obtained in T4 (100% RS) after 29 days, whereas the longest harvesting day was obtained in T1 (90% SD + 10% rice bran) after 51 days. The highest yield was obtained in T4. Nutrition analysis showed significant difference among the treatments. The highest amounts of protein (26%) and ash (1.29%) were found in T5. Overall, the results showed that mushroom yield performance was good in RS but nutritional content was the highest in PPF. Therefore, RS and PPF have good impact for mushroom growers either in commercial production or in functional food industry to reduce SD dependency.